FAKTOR – FAKTOR YANG MEMPENGARUHI IMPOR BERAS INDONESIA - Jumai Nijar; Tarmizi Abbas (LPPM Universitas Malikussaleh – Indonesia, 2019)
This study aims to determine the factors that influence rice imports in Indonesia. The data used in this study are time series in the period 1999-2017. The analytical model used in this study is the Multiple Linear Regression Model and the ARDL Model. The results showed that are that together the Inflation, Exchange Rate and Retail Prices variables had a positive and significant effect on Rice Imports. While partially Inflation and retail prices each had a positive and significant effect on the Import of Rice. There is no influence exchange rate and negative effect on Rice Imports. From the results of the ARDL model it can be seen that the long-run and short-run inflation variables had no significant and negative effect on rice imports and the long-run exchange rate variable had a significant and negative effect on rice imports. While in the short run the exchange rate variable had no effect on rice imports, while the retail price variable in the short and long run had a significant and positive effect on rice imports in Indonesia.